Analisis Perbandingan Waktu dan Biaya Pekerjaan Pelat Lantai Menggunakan Metode Konvensional dan Precast Half Slab pada Rumah Sakit X - Febrio Maulana; Ari Syaiful Rahman Arifin; Muvi Yandra; Fani Keprila Prima (MASALIQ, 2026)
The selection of the floor slab construction method has become an important issue in multi-storey building projects because it directly affects time and cost efficiency, while studies specifically comparing conventional and precast half slab methods in hospital buildings remain relatively limited. This study aims to analyze the comparison of time and cost in floor slab work using conventional and precast half slab methods in the construction of Hospital X. This study employed a quantitative approach with a case study design. Data were collected through field observation, interviews, and project documentation, and were then analyzed using descriptive comparative analysis. The results showed that the conventional method required a duration of 26 days per floor at a cost of Rp594,552,359, whereas the precast half slab method required a duration of 18 days per floor at a cost of Rp425,251,134. These findings indicate that the precast half slab method was 8 days faster and saved Rp169,301,225 compared with the conventional method. Thus, this study confirms that the precast half slab method is more efficient in terms of time and cost, and provides a practical contribution for contractors and project owners in determining a more effective floor slab work method for hospital buildings and multi-storey buildings.